2022
DOI: 10.1111/1744-7917.13033
|View full text |Cite
|
Sign up to set email alerts
|

Efficient polymer‐mediated delivery system for thiocyclam: Nanometerization remarkably improves the bioactivity toward green peach aphids

Abstract: The unscientific application of synthetic pesticides has brought various negative effects on the environment, hindering the sustainable development of agriculture. Nanoparticles can be applied as carriers to improve pesticide delivery, showing great potential in the development of pesticide formulation in recent years. Herein, a star polymer (SPc) was constructed as an efficient pesticide nanocarrier/adjuvant that could spontaneously assemble with thiocyclam or monosultap into a complex, through hydrophobic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 67 publications
6
26
0
Order By: Relevance
“…Our results revealed that there was a strong hydrogen bonding and Van der Waals forces between CNAP and SPc, and we deduced the amide NH of CNAP and carbonyl groups or tertiary amines of SPc played an important role in the self-assembly of CNAP/SPc complex. Consistent with previous studies, the SPc can assemble with dinotefuran, monosultap, avermectin and chitosan through hydrogen bond and Van der Waals forces [ 25 , 32 , 33 , 57 ]. Meanwhile, the SPc can also combine with thiocyclam, eugenol, thiamethoxam, matrine and osthole through different interaction forces, such as electrostatic interaction and hydrophobic association [ 25 , 29 , 30 , 31 , 33 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results revealed that there was a strong hydrogen bonding and Van der Waals forces between CNAP and SPc, and we deduced the amide NH of CNAP and carbonyl groups or tertiary amines of SPc played an important role in the self-assembly of CNAP/SPc complex. Consistent with previous studies, the SPc can assemble with dinotefuran, monosultap, avermectin and chitosan through hydrogen bond and Van der Waals forces [ 25 , 32 , 33 , 57 ]. Meanwhile, the SPc can also combine with thiocyclam, eugenol, thiamethoxam, matrine and osthole through different interaction forces, such as electrostatic interaction and hydrophobic association [ 25 , 29 , 30 , 31 , 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…As a gene/pesticide nanocarrier, the SPc can be complexed with various exogenous substances for enhanced delivery and bioactivity [ 24 , 25 , 29 , 30 ]. The current study illustrated that the pesticide loading content of SPc toward CNAP was 24.79%, which was higher than those of osthole (17.09%), thiamethoxam (20.63%), monosultap (19.3%), and dinotefuran (17.41%) [ 30 , 31 , 32 , 33 ]. The binding affinity of CNAP with SPc was then analyzed using a high-accuracy method ITC [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations